Fault Injection in Production. - Allspaw, John (Communications of the ACM, 2012)
The article discusses resiliency in computer systems and Internet infrastructure engineering, arguing that systems should be tested before they reach production stages and focusing on "Game Day" fault testing processes employed at the Internet merchant Etsy. Topics include systems integration and degradation, fault integration as a business continuity plan (BCP), risk, and the potential decrease of anxiety that can result from testing a system before its launch. The process of testing an Internet payment system, including its security and processing components, is described.